An overview of solid waste management and privatization in kingdom of Bahrain - Fahmi Jamal, Hala; Abd El-Fattah, Ahmed (Frontiers in Environmental Science, 2023)
Waste management (WS) has been identified as one of Bahrain's most pressing concerns owing to the potential negative consequences for the country. Data collected over the last thirty years show considerable growth in waste amount created in the country throughout the sectors of residential, commercial, institutional, building and demolition, municipal services, public places, treatment plant sites, manufacturing, and crop residues. The restricted location space, characterised by Bahrain's tiny geographic area, is the most significant element contributing to the difficulty of controlling the government's rising waste buildup and developing Sustainable Waste Management (SWM) systems. As a result, the study focuses on the rising have to upgrade the government's present Municipal Solid Waste Management (MSWM) system. Which the study discussed the MSWM in Bahrain that was consisted of Solid Waste generation, composition, and characteristics and also discussed the waste collection, transportation, disposal and regulations and institutions in the Kingdom of Bahrain. Furthermore, The study focused on the general views about waste management and privatization. Also, discuessed MSWM and sustainable development goals (SDGs) and privatization as a private sector in the context of SDGs.